FAST METHOD OF NON-CONTACT MICROWAVE MEASUREMENTS OF ELECTRICAL PARAMETERS OF COMPACT SAMPLES - N. A. Poklonski; A. I. Siahlo; V. T. Shnitko; V. A. Merkulov; O. M. Davidenia; A. I. Kovalev (Приборы и методы измерений)
The setup with a reflective microwave H101 resonator for the non-contact measurements of the electrical parameters of compact samples (the diameter less than 5 mm) is constructed. An analytical expression for calculation of the microwave power reflection coefficient by the H101 resonator with the sample being inside the resonator with respect to the dielectric permittivity and conductivity of sample is obtained. The dependence of the microwave power reflection on the diameter of the metallic and glassy globs freely falling through the resonator is experimentally found. an>